If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (y + 4)(y + -1) = 0 Reorder the terms: (4 + y)(y + -1) = 0 Reorder the terms: (4 + y)(-1 + y) = 0 Multiply (4 + y) * (-1 + y) (4(-1 + y) + y(-1 + y)) = 0 ((-1 * 4 + y * 4) + y(-1 + y)) = 0 ((-4 + 4y) + y(-1 + y)) = 0 (-4 + 4y + (-1 * y + y * y)) = 0 (-4 + 4y + (-1y + y2)) = 0 Combine like terms: 4y + -1y = 3y (-4 + 3y + y2) = 0 Solving -4 + 3y + y2 = 0 Solving for variable 'y'. Factor a trinomial. (-4 + -1y)(1 + -1y) = 0Subproblem 1
Set the factor '(-4 + -1y)' equal to zero and attempt to solve: Simplifying -4 + -1y = 0 Solving -4 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1y = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1y = 0 + 4 -1y = 0 + 4 Combine like terms: 0 + 4 = 4 -1y = 4 Divide each side by '-1'. y = -4 Simplifying y = -4Subproblem 2
Set the factor '(1 + -1y)' equal to zero and attempt to solve: Simplifying 1 + -1y = 0 Solving 1 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1y = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1y = 0 + -1 -1y = 0 + -1 Combine like terms: 0 + -1 = -1 -1y = -1 Divide each side by '-1'. y = 1 Simplifying y = 1Solution
y = {-4, 1}
| 4x-3=180-2x | | x+x+10+90=360 | | 1-3x=4-7 | | 18x^2-63+0=0 | | 5(y-4)=y | | 2x^2=91 | | 3x+12+2x=15 | | y=-2(4)+7 | | 3(x+7)-9=4x+12 | | 7b+3c-2b-3c= | | 16x+32=-14x-6 | | 3x+6=2x-9 | | X+(x*0.2)=8000 | | 3(2x-5)=8x-7 | | 72-6=6-8x | | 10a+14b+3c+2a= | | x*(x*0.2)=8000 | | 4x+9+3x+12=56 | | 3z+1=0 | | 7(9+3x)=294 | | 7(2x-1)=15 | | 0.05x+y+5z=100 | | 3ln^2x=0 | | 3x^2+4y^2-6x+8y-5=0 | | X+x+4+2x+8=180 | | x+x+4+2x+8= | | 4x^3-34x=0 | | 15+-5x=125 | | 15+-5=125 | | -7m+9=39-2m | | 8(3m-4)-10m= | | p-17=-54 |